Elizabethkingia Meningoseptica: An Emerging Nosocomial Pathogen Causing Septicemia in Critically Ill Patients - Sahu, Manoj Kumar (Indian J Crit Care Med, 2019)
Elizabethkingia meningoseptica (E. meningoseptica), is an opportunistic Gram-negative bacteria, normally found in water and soil, notorious for causing nosocomial infections in extremes of ages and immunocompromised patients. It is now emerging as a serious nosocomial pathogen, intrinsically resistant to several commonly used antibiotics (e.g. beta-lactams, aminoglycosides, carbapenems and colistin etc. and a cause of high mortality in critically ill patients in intensive care units (ICUs). We report the first case of E. meningoseptica sepsis in a 5 month old child after open heart surgery for transposition of great arteries, initially on extracorporeal membrane oxygenation, then prolonged mechanical ventilation, with various invasive devices, inotropes and exposed to broad spectrum antibiotics in our ICU. The case highlights the potential risk factors responsible for E.meningoseptica sepsis. Its unusual pattern of resistance to many commonly used antibiotics makes this organism difficult to treat. HOW TO CITE THIS ARTICLE: Sahu MK, Balasubramaniam U et al. Elizabethkingia Meningoseptica: An Emerging Nosocomial Pathogen Causing Septicemia in Critically Ill Patients. Indian J of Crit Care Med 2019;23(2):104-105.